1996
DOI: 10.1002/bies.950181010
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear transplantation in mammals: Remodelling of transplanted nuclei under the influence of maturation promoting factor

Abstract: Whilst the role of Maturation or M-phase Promoting Factor (MPF) as a universal M-phase regulator is well documented, much less attention has been paid to its role in nuclear transplantation experiments and especially to its influence upon remodelling of transplanted nuclei. There is currently wide acceptance that successful nuclear transplantation using differentiated nuclei is possible only in a cytoplasmic environment that is capable of inducing rapid nuclear de-differentiation to a pronuclear-like form. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 40 publications
1
30
0
Order By: Relevance
“…This discrepancy may be due to the MPF activity [34]. In the present study, both an intact nuclear envelope and NEBD with PCC were observed when either serum fed or starved donor cells were introduced into MII cytoplasts.…”
Section: Discussionmentioning
confidence: 50%
“…This discrepancy may be due to the MPF activity [34]. In the present study, both an intact nuclear envelope and NEBD with PCC were observed when either serum fed or starved donor cells were introduced into MII cytoplasts.…”
Section: Discussionmentioning
confidence: 50%
“…For successful nuclear transfer and development of the resulting reconstructed egg, the properties of the donor nucleus have to become like those of the normal zygotic nucleus and the normal kinetics of remodeling occurs during the one-cell stage, and this appears to be the determining factor for the normal onset of gene expression (PintoCorreia et al 1995, Renard 1998. This procedure requires co-operation of the activities of cell cycle regulators (Fulka et al 1996) and maternal stores of protein (Almouzni & Wolffe 1993). It is assumed that the somatic cell nuclei are mysteriously converted to embryonic genomes, which then passively progress down the developmental path leading to a new individual.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as soon as fish eggs encounter with water, they are activated immediately and coupled with the subsequent decline of maturation promoting factor (MPF). The MPF is considered as a key factor for the reprogramming of donor nucleus in the nuclear transplants [22] .…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as soon as fish eggs encounter with water, they are activated immediately and coupled with the subsequent decline of maturation promoting factor (MPF). The MPF is considered as a key factor for the reprogramming of donor nucleus in the nuclear transplants [22] .To examine the onset of hGH transcription, samples were taken from early-blastula stage in nuclear-transferred embryos supported by transgenic F 4 embryonic nuclei, and from 16-cell stage in nuclear-transferred embryos supported by transgenic F 4 tail-fin nuclei. It was unexpected that all the sampled embryos had turned on the transcriptional activity of hGH.…”
mentioning
confidence: 99%